PENERAPAN MODEL PEMBELAJARAN DEEP LEARNING MAHASISWA PLP UNIVERSITAS PGRI PALEMBANG DI SMP NEGERI 42 PALEMBANG - Zahra Athirah; Zahra Safitri Sinaga; Dara Luri Maharani; Mutiara Dewi Mavinka; Afifah Anggraeni; Inda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The School Field Introduction Program (PLP) is an activity aimed at providing students with real-world experience in implementing the learning process at school. This activity is carried out by students of Universitas PGRI Palembang at SMP Negeri 42 Palembang, implementing various learning models tailored to student needs and learning objectives. The goal of this activity is to improve student teaching skills, develop students' ability to understand the material, and create an active, creative, and enjoyable learning process